2017
DOI: 10.1007/s11205-017-1629-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Life Satisfaction of Immigrants and Natives Across Europe: The Role of Social Contacts

Abstract: Research on immigrants’ assimilation is widespread both in the U.S. and Europe. While it has been extensively studied how immigrants fare compared to natives on socio-economic indicators, few studies have focussed on immigrants’ perception of their position. In this paper we focus on comparing life satisfaction of immigrants and natives across Europe and on the role of social embeddedness. Using data from the first six rounds (2002–2012) of the European Social Survey, a repeated cross-sectional survey, we find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 58 publications
6
52
3
3
Order By: Relevance
“…Moreover, majority Whites in the United States, but not the United Kingdom, perceive normative multicultural ideology to be stronger than do minorities (Ward, Stuart, & Watters, ). With respect to social and psychological outcomes, national surveys have shown that there are often asymmetries in intergroup perceptions with majorities tending to be viewed more positively by minorities than the reverse (Sibley & Ward, ), and life satisfaction has been found to be lower in immigrants than in native‐borns (Arpino & de Valk, ).…”
Section: Psychological Contributions To the Multiculturalism Debatementioning
confidence: 99%
“…Moreover, majority Whites in the United States, but not the United Kingdom, perceive normative multicultural ideology to be stronger than do minorities (Ward, Stuart, & Watters, ). With respect to social and psychological outcomes, national surveys have shown that there are often asymmetries in intergroup perceptions with majorities tending to be viewed more positively by minorities than the reverse (Sibley & Ward, ), and life satisfaction has been found to be lower in immigrants than in native‐borns (Arpino & de Valk, ).…”
Section: Psychological Contributions To the Multiculturalism Debatementioning
confidence: 99%
“…The two extreme solutions are associated with statistically indistinguishable levels of satisfaction. Although the magnitude of the association between the unpaid childcare ratio and satisfaction with work-family balance at first sight does not seem to be strong, comparing the satisfaction levels at the pick and at the extremes gives a difference of about 0.2 points, which corresponds to the typical magnitude of important effects found in other studies on the same or similar outcomes (e.g., Arpino and de Valk 2018;Matysiak, Mencarini, and Vignoli 2016). Notes: * p = .05; ** p = .01; ***; p = .001.…”
Section: Ratio Of Unpaid Childcare and Satisfaction With Work-family mentioning
confidence: 66%
“…Thus, the environmental context of Israel, as a society between traditional values of family relations and support and modern values of individualization and separation (Clarfield et al, 2018), provides a context for this finding. It seems that Israeli older adults are seeking social contacts and social activities that reflect the value of collectivism (Arpino & de Valk, 2018). Indeed, it was found that many Israeli residents and their adult children were quite enthusiastic about the opportunity for residents to reengage in social relations and activities, arguing that the CCRC fulfills their expectations for social interaction (Ayalon & Green, 2013).…”
Section: Discussionmentioning
confidence: 99%